De maestros de enseñanza a formadores de campo en la pasantía supervisada - Benites, Larissa Cerignoni [UNESP]; Sarti, Flavia Medeiros [UNESP]; de Souza Neto, Samuel [UNESP] (FapUNIFESP (SciELO), 2015)
This article presents the results of the national and international literature review on supervised internship and the role of the cooperating-teacher who receives and monitors the teaching training of interns in the school. The teacher, initially trained to provide basic education, receives interns in his/her class without necessarily relying on guidance on how to perform this formative function. The studies investigated revealed the learning from the performance of this function follows those of vocational schools, mainly through transmission of exemplary practices. These training practices clash with certain proposals for teacher education that are being established in the current educational context, marked by speeches on the professionalization of teaching.
De mestres de ensino a formadores de campo no estágio supervisionado
From teacher masters to field formers in the supervised internship
Keywords: Educational practice; Internship programmes; Teacher education; Teachers